The role of national culture in shaping health workforce collaboration: Lessons learned from a case study on attitudes to interprofessional education in Malta. Issue 10 (October 2018) - Bonello, Marjorie; Morris, Jane; Azzopardi Muscat, Natasha
Highlights: Interprofessional education could prepare healthcare professionals to work across professional silos. It necessitates a shift from traditional uniprofessional practices towards integrative curricula approaches. Hofstede's cultural dimensions were employed to understand cultural resistances. Lessons learnt may have implications for transferability of health system reforms. Abstract: The World Health Organisation identifies interprofessional education (IPE) as a key element for preparing a collaborative workforce. However, global implementation remains challenging due to individual, professional and organisational barriers. A qualitative case study explored the concept of introducing an undergraduate IPE programme at the Faculty of Health Sciences, University of Malta. A combination of in-depth interviews and focus groups were conducted with a sample of sixty-four academics, health and education policy makers and newly qualified health professionals. The findings suggest that while participants support the notion of IPE, they identify multiple barriers that would challenge implementation. This includes particular cultural norms and values which participants perceived would conflict with IPE. These findings were interpreted through Hofstede's theory of cultural dimensions as a means of theorising about the role that culture could play in implementing such an approach. This study contributes to the health policy debate by highlighting the potential impact of national culture in the planning, development and delivery of collaborative initiatives. It also highlights new insights for European small states and other countries by providing a lens through which culture needs to be taken into account in the transfer of innovation across health systems.